1996
DOI: 10.1002/(sici)1097-010x(19960215)274:3<171::aid-jez4>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of growth hormone nycthemeral plasma profiles in catheterized rainbow trout (Oncorhynchus mykiss)

Abstract: This study was conducted in order to characterize the nycthemeral plasma profiles of growth hormone (GH) in 41 prepubertal (2+) rainbow trout (Oncorhynchus mykiss). The possible influences of day‐night alternation and of the food factor (quantity ingested, timing of the feed) on these plasma profiles were also analysed. Blood samples were taken every hour during a 24‐hour period through a catheter inserted in the dorsal aorta. An assay of cortisol levels showed that the fish were in satisfactory physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…This could explain the magnitude of the standard errors due to individual variability. Nycthemeral variations of cortisol have been reported in freshwater fish by Pickering & Pottinger (1983) and Gomez et al (1996), who concluded that cortisol increases are intrinsic phenomena not caused by stress. To our knowledge similar studies have not been made with seawater fish.…”
Section: J O O~mentioning
confidence: 82%
“…This could explain the magnitude of the standard errors due to individual variability. Nycthemeral variations of cortisol have been reported in freshwater fish by Pickering & Pottinger (1983) and Gomez et al (1996), who concluded that cortisol increases are intrinsic phenomena not caused by stress. To our knowledge similar studies have not been made with seawater fish.…”
Section: J O O~mentioning
confidence: 82%
“…Niu et al (1993) recorded the pulsatile pattern of GH secretion in rainbow trout. However, Gomez et al (1996) did not record any significant rhythm in GH secretion, yet the plasma level of GH fluctuated over the day-night cycle, although peaks occurred irregularly and asynchronously in individual rainbow trout. Reddy and Leatherland (1995) have reported significant postprandial peaks in plasma GH in rainbow trout that phase shifted with time of feeding.…”
Section: Discussionmentioning
confidence: 84%
“…They recorded either one episode (single or several pulses clustered) or two episodes with a 2.6-h interval. A diurnal variation in GH secretion in rainbow trout has also been demonstrated, but data are highly variable (Gomez et al 1996). Le Bail et al (1991) have reported daily fluctuations in plasma GH in both sexes of Chinook salmon with individual variations with regard to frequency and timing of GH peaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les niveaux de Cortisol élevés observés chez les poissons du lot péché au petit jour, juste avant le transport, sont de l'ordre des valeurs maximales rapportées par GOMEZ et al (1996), pendant la nuit, chez des truites arc-en-ciel équipées d'un cathéter pour la prise de sang. Ces niveaux pourraient donc refléter aussi bien des variations naturelles qu'un premier stress lié à la pêche.…”
Section: Discussion -Conclusionunclassified